2017
DOI: 10.1007/s40092-017-0218-6
|View full text |Cite
|
Sign up to set email alerts
|

A model for distribution centers location-routing problem on a multimodal transportation network with a meta-heuristic solving approach

Abstract: Nowadays, organizations have to compete with different competitors in regional, national and international levels, so they have to improve their competition capabilities to survive against competitors. Undertaking activities on a global scale requires a proper distribution system which could take advantages of different transportation modes. Accordingly, the present paper addresses a location-routing problem on multimodal transportation network. The introduced problem follows four objectives simultaneously whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…As presented in Table 7, 67.12% of the classified articles developed at least one heuristics technique based on a metaheuristic framework. Figures 3 and 4 showed that the variants of simulated annealing (e.g., Yu and Lin, 2015;Ferreira and Queiroz, 2018) and genetic algorithm (e.g., Hiassat et al, 2017;Fazayeli et al, 2018aFazayeli et al, , 2018b are favored for single-objective LRP, while nondominated sorting genetic algorithm II (NSGA-II) (e.g., Wang et al, 2018b;Rabbani et al, 2019) and multiobjective particle swarm optimization (e.g., Tang et al, 2016;Vahdani et al, 2018a) are the preferred frameworks for MOLRP. This is admittedly reasonable since the aforementioned metaheuristics are historically classical (Sörensen et al, 2018) and commonly used as a benchmark for proposing a new algorithm.…”
Section: Solution Approachmentioning
confidence: 99%
“…As presented in Table 7, 67.12% of the classified articles developed at least one heuristics technique based on a metaheuristic framework. Figures 3 and 4 showed that the variants of simulated annealing (e.g., Yu and Lin, 2015;Ferreira and Queiroz, 2018) and genetic algorithm (e.g., Hiassat et al, 2017;Fazayeli et al, 2018aFazayeli et al, , 2018b are favored for single-objective LRP, while nondominated sorting genetic algorithm II (NSGA-II) (e.g., Wang et al, 2018b;Rabbani et al, 2019) and multiobjective particle swarm optimization (e.g., Tang et al, 2016;Vahdani et al, 2018a) are the preferred frameworks for MOLRP. This is admittedly reasonable since the aforementioned metaheuristics are historically classical (Sörensen et al, 2018) and commonly used as a benchmark for proposing a new algorithm.…”
Section: Solution Approachmentioning
confidence: 99%
“…The second is that they can provide an exact benchmark to verify the efficiency and accuracy of the heuristic algorithms [67]. Fazayeli et al [68] also highlighted that the development of an exact algorithm and the comparison between the algorithms will be their future work for the location-routing problem on a multimodal transportation network.…”
Section: An Exact Solution Strategymentioning
confidence: 99%
“…Recent research has enriched and expanded the LRP. Fazayeli et al [25] presented an LRP with time windows and fuzzy demand, involving a plan for depot establishment in customer regions. Our study has similarities with the LRP, involving multiple multimodal stations and the selection of multiple intercontinental train departure times.…”
Section: B Intercontinental Multimodal Routing Problemmentioning
confidence: 99%
“…In this problem, tractors depart from the DMS without containers. Constraints (20) to (25) show the relationship between the departure time in the DMS and the arrival time in the next station. According to the constraint where a tractor cannot cover two continuous routes without a semitrailer, the next station should be a DHS.…”
Section: ) Constraints Of Fuzzy Timementioning
confidence: 99%
See 1 more Smart Citation